Mining's legacy: unraveling the impacts of acid mine drainage on the rivers and streams of the Santa Catarina coal region, Brazil - CARDOSO, Albert Teixeira (2024)
Acid Mine Drainage (AMD) is a major environmental concern associated with coal mining activities, leading to the deterioration of water quality and posing significant risks to aquatic ecosystems and human health. In this study, we analyzed the physicochemical parameters of water samples collected from rivers and streams affected by mining in the Santa Catarina coal region, Brazil, to assess the extent and severity of AMD impact. Our findings reveal a substantial increase in element concentrations, including Fe, Mn, Al, and major cations (Na, Mg, Ca, and K), with some values exceeding background levels by several orders of magnitude. The majority of the samples exhibited acidic pH values, with only 24% and 34% within the limits established by the Ministry of Health and the geochemical background, respectively. Strong correlations between physicochemical parameters, such as pH and EH, and between acidity, sulfate, and metals, highlight the role of pyrite oxidation and mineral dissolution in generating AMD. Although most samples presented values within the established limits for toxic metals (Cu, Cd, Pb, As, and Hg), high concentrations of Zn were observed, exceeding regulatory and background limits. The results of this study emphasize the need for continuous monitoring and assessment of water quality in the region and contribute to a deeper understanding of the extent and severity of AMD in the Santa Catarina coal region.